Associations of site-specific CD4+-T-cell hypomethylation within CD40-ligand promotor and enhancer regions with disease activity of women with systemic lupus erythematosus. (January 2021) - Vordenbäumen, Stefan; Rosenbaum, Anna; Gebhard, Claudia; Raithel, Johanna; Sokolowski, Alexander; Düsing, Christina; Chehab, Gamal; Richter, Jutta G; Brinks, Ralph; Rehli, Michael; Schneider, Matthias
Objective: To comprehensively assess associations of site-specific CD4 + -T-cell hypomethylation of the CD40-Ligand gene ( CD40L ) with disease activity of women with systemic lupus erythematosus (SLE). Methods: CpG-sites within the DNA of the promotor and two enhancer regions (n = 22) of CD40L were identified and numbered consecutively. The rate of methylated DNA in isolated CD4 + -T-cells of women with SLE were quantified for each methylation site by MALDI-TOF. Disease activity was assessed by SLE Disease Activity Index (SLEDAI). Associations of site-specific methylation rates with the SLEDAI scores were assessed by linear regression modelling. P values were adjusted according to Bonferroni-Holm as indicated. Results: 60 female SLE patients participated in the study (age 45.7 ± 11.1 years, disease duration 17.0 ± 8.3 years). Significant associations to the SLEDAI were noted for CpG22 hypomethylation of the promotor (β = −40.1, p = 0.017, adjusted p = 0.027), trends were noted for CpG17 hypomethylation of the promotor (β = −30.5, p = 0.032, adjusted p = 0.6), and for CpG11 hypermethylation of the second enhancer (β = 15.0, p = 0.046, adjusted p = 0.8). Conclusion: Site-specific hypomethylation of the CD40L promotor in CD4 + -T-cells show associations with disease activity in female SLE patients.